Koledarski čas in učinki dela z žičnimi napravami syncrofalke na tolminskem - Medved, Mirko (Zbornik gozdarstva in lesarstva, 2005)
The article presents an analysis of calendar times and work performance of twoSyncrofalke cable cranes in Slovenia - the Tolminsko region. Calendar time is dealt with in accordance of the international IUFRO methodology. It is divided into workplace time, i.e. 261 days, and non-workplace time, which is 104 days. For each day, 8 hours are taken into account, which is in fact stipulated in the national work legislation, and the workplace time therefore amounts to 2,088 hours per year. Calendar time for the two cable cranes was monitored from the beginning of July 2002 till the end of March 2004, a total of 1,270 calendar days for both cable cranes. During this time, the cable cranes operated 709 days on 79 lines, or 204 days per cable crane annually, 132 of these for skidding. Average line length, which from the tower to the last tailblock measured 305 m on average, had 0.62 intermediate support per line. Average yarding distance per skyline was 208 m, the bunching distance 34m. The share of uphill yarding lines was 62 %. Average volume of wood was 1.04 m3 (1.12 t) per cycle and 300 m3 per line, 83 % of which went to deciduous trees. Calendar time monitoring, which was carried out by the cable crane crew, is a good expedient for long-term monitoring and analyses of a series of parameters of work performance, of the effects achieved by the machine, for comparisons between different machines, and for the final assessment of work payment.
Keywords: delovni čas; delovni proces; spravilo lesa; študij dela; Tolminsko; žičnice